2016
DOI: 10.1308/rcsann.2016.0070
|View full text |Cite
|
Sign up to set email alerts
|

An audit of consent for allograft use in elective orthopaedic surgery

Abstract: Introduction Patients receiving musculoskeletal allografts may be at risk of postoperative infection. The General Medical Council guidelines on consent highlight the importance of providing patients with the information they want or need on any proposed investigation or treatment, including any potential adverse outcomes. With the increased cost of defending medicolegal claims, it is paramount that adequate, clear informed patient consent be documented. Methods We retrospectively examined the patterns of infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…For this reason, they were analysed separately from other specific risks. Media reports have heightened public awareness of the risk of allograft, and other studies have reported poor compliance of documenting consent for its risks 54,55 . The recording of consent for the use of human allograft bone was introduced onto the institutional consent form (Supplementary Information 1) in 2018 after a patient complaint that led to an enquiry by the New Zealand Health and Disability Commissioner 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, they were analysed separately from other specific risks. Media reports have heightened public awareness of the risk of allograft, and other studies have reported poor compliance of documenting consent for its risks 54,55 . The recording of consent for the use of human allograft bone was introduced onto the institutional consent form (Supplementary Information 1) in 2018 after a patient complaint that led to an enquiry by the New Zealand Health and Disability Commissioner 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Media reports have heightened public awareness of the risk of allograft, and other studies have reported poor compliance of documenting consent for its risks. 54,55 The recording of consent for the use of human allograft bone was introduced onto the institutional consent form (Supplementary Information 1) in 2018 after a patient complaint that led to an enquiry by the New Zealand Health and Disability Commissioner. 56 The case centred on a patient who underwent spinal surgery with allograft and complained that they were not consented preoperatively for the use of allograft.…”
Section: Discussionmentioning
confidence: 99%
“…23 Audit and feedback mechanism, supplemented by several measures including educational activities, appropriate incentives and disincentives, is likely to result in meaningful behavioural change. 24,25 A qualitative audit to ascertain the clinician acceptance and compliance with structured clinical proforma versus freehand case notes is recommended to guide the flexible design of the proforma in future.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback referred to information about the performance of an individual from an outside source; feedback was conducted in two forms: positive feedback (reinforcing or positive) and negative (constructive or corrective). 13,14 Positive feedback utilised a variety of positive incentives including monetary (pay-forperformance, gift cards, and bonuses) and non-monetary (flexible working hours, vacation days) approaches to reinforce targeted behaviour. 16,17 To amplify the impact of the A&F intervention, an educational guideline assisting residents Implementing the interventions Source of feedback -The head of the surgery department worked as a facilitator and rater for residents' MRD.…”
Section: Developing the Interventionmentioning
confidence: 99%
“…12 Evidence suggests that A&F has a signifi cant impact on changing the behaviour of physicians and is considered to be one of the best approaches to improve professional behaviour and performance in healthcare organisations. 13,14 This study aimed to investigate the effects of multifaceted mechanisms on the improvement of medical records documentation prepared by surgical residents at a tertiary university hospital.…”
Section: Introductionmentioning
confidence: 99%